Effects of cleaning corn on nursery pig growth performance - Tischhauser, Lyndy M.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2018)
Prior to storage, grain producers clean corn to reduce broken corn and foreign material. Recent research from our laboratory demonstrated that cleaning corn reduces fumonisin concentration by 45 to 60%. However, it is unknown if cleaning corn affects nursery pig growth performance. Therefore, the objective of this experiment was to determine the effect of cleaning corn in mash diets or pelleted diets by using two different type of pellet mills to provide different quality pellets. A total of 360 nursery pigs (initially 8.8 kg BW) were utilized in a 28-d-experiment. The diets consisted of a 2 × 3 factorial with corn type (clean vs. unclean) and feed form (mash vs. medium quality pellets vs. low quality pellets) created six experimental treatments: 1) unclean-mash, 2) clean-mash 3) unclean-medium quality pellet, 4) clean-medium quality pellet, 5) unclean-low quality pellet, 6) clean-low quality pellet feed. Corn particle size (400-500µm), conditioning temperature (85°C ± 2°C), and conditioner retention time (30s) were held constant across all pelleted diets. Data were analyzed using the GLIMMIX procedure of SAS. Neither cleaning corn nor the interaction affected (P > 0.25) growth performance. Overall, no significant differences were determined (P > 0.089) between medium quality and low quality pellets. Pigs fed pelleted diets had lower (P < 0.05; 0.38 vs. 0.41 kg/d for pigs fed pelleted vs. mash feed, respectively) ADG from d 0 to 14, but higher (P = 0.001; 0.71 vs. 0.67 kg/d for pigs fed pelleted vs. mash feed, respectively) ADG from d 14 to 28. Thus, there was no overall impact (P > 0.05) of feed form on ADG. Pellet mill difference did not impact (P = 0.897) ADG either. For both phases and the overall experiment, pigs fed pelleted diets had lower ADFI than those fed mash diets (P < 0.0001; 0.76 vs. 0.82 kg/d for pigs fed pelleted vs. mash feed, respectively). From d 0 to 14, treatment did not impact (P = 0.539) G:F. From d 14 to 28 and the overall experiment, pigs fed pelleted diets had improved (P < 0.0001; 0.71 vs. 0.65 for pigs fed pelleted vs. mash diets, respectively) GF than those fed mash diets. In summary, cleaning corn does not affect the growth performance of nursery pigs, but pelleting improves nursery pig feed efficiency.
Keywords: Spring 2018